Pelestarian Lingkungan melalui Program Penanaman Pohon Jati Berbasis Partisipasi Masyarakat di Kabupaten Blitar - Endang Shyta Triana (JURPIKAT, 2026)
This community service activity was carried out in rural areas of Blitar Regency, East Java, with the aim of increasing environmental awareness and opening economic opportunities through participatory teak planting. The program was motivated by the low utilization of vacant land and limited employment opportunities for the village community, the majority of whom work as farm laborers. The activities were carried out on land covering more than 10 hectares spread across several villages, involving 20 local workers, consisting of core and seasonal workers. The methods used included environmental education, socialization of the benefits of teak wood, technical training on planting and maintenance, and collective tree planting. A participatory approach was key to fostering a sense of community responsibility. The results showed an increased community understanding of environmental conservation and long-term economic benefits. In addition, the program also created local jobs and reduced the need to migrate, thus creating sustainable social, economic, and environmental impacts.